2012
DOI: 10.1097/imi.0b013e3182552ade
|View full text |Cite
|
Sign up to set email alerts
|

The Early Inflammatory Response in a Mini–Cardiopulmonary Bypass System a Prospective Randomized Study

Abstract: Objective The aim of this study was to compare the early systemic inflammatory response of the Resting Heart System (RHS; Medtronic, Minneapolis, MN USA), a miniaturized cardiopulmonary bypass (CPB) system, with two groups using a standard extracorporeal circulation system during on-pump coronary artery bypass grafting (CABG) surgery. Methods A total of 60 consecutive patients requiring CABG were prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Increased neutrophil margination into several tissues, particularly the lungs, has been described during ECMO, both in animal models and in neonates [14, 15, 30, 94]. Overall, neutrophil numbers increase after the initiation of extracorporeal circulation [95] and neutrophil function appears to be preserved [25, 28]. This is despite the reported adverse effects of ECMO on leukocyte rheology [96].…”
Section: Ecmo the Endothelium And Leukocytesmentioning
confidence: 99%
“…Increased neutrophil margination into several tissues, particularly the lungs, has been described during ECMO, both in animal models and in neonates [14, 15, 30, 94]. Overall, neutrophil numbers increase after the initiation of extracorporeal circulation [95] and neutrophil function appears to be preserved [25, 28]. This is despite the reported adverse effects of ECMO on leukocyte rheology [96].…”
Section: Ecmo the Endothelium And Leukocytesmentioning
confidence: 99%
“…The presence of barriers separating the blood from the air and decreasing the surface of contact of artificial materials with the blood gives measurable benefits, such as reduction in the incidence of the systemic inflammatory response syndrome (SIRS), although SIRS itself occurs almost always, with a variable degree of severity [1,2]. 'Mini-CPB' significantly decreases the incidence of early inflammatory response, which was confirmed in a randomised trial by Kiaii et al [3] and in other studies [1,4]. In our study we found earlier rise of the CRP and procalcitonin levels as well as leukocyte count in the 'mini-CPB' group than in the control group by approximately 24 h, with a gradual decrease thereafter in both groups.…”
Section: Discussionmentioning
confidence: 64%
“…This is supported also by the study by Halonen et al [19] in which the incidence of postoperative AF was significantly lower in patients treated with intravenous metoprolol as compared to metoprolol by mouth. Evolution of the cardiopulmonary bypass has emerged new techniques such as MECC to reduce the inflammatory response follow cardiac surgery [21][22][23]. Reducing the surface area of the circuit and removing the blood-air interface potentially offers several benefits compared to CECC including reduced hemodilution, postbypass coagulopathy, and inflammatory response [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…New techniques, such as miniaturized ECC (MECC), have been developed to reduce blood-air and blood-artificial material contact and, thus, inflammatory response compared to conventional ECC (CECC) [21][22][23]. In addition, an increasing number of CABG procedures are performed without any ECC (OPCAB) aiming to less surgical trauma and even less inflammatory reaction than with CECC or MECC [24,25].…”
mentioning
confidence: 99%